Express Yourself! Pelatihan Public Speaking untuk Remaja di SMP Cokroaminoto Tamalanrea Makassar - Oky Nur Pratiwi Johansyah; Darman Manda; Sulmiah Sulmiah; Asri Nur Aina; Herman Dody (PT. Global Research Collaboration, 2024)
The training ‘Express Yourself! Public Speaking Training for Teenagers at Cokroaminoto Junior High School Tamalanrea, Makassar‘ aimed to improve students’ Public Speaking skills and confidence. The training was attended by approximately 50 students as well as several teachers, with implementation assistance by university students. The training method included theory sessions, practical exercises, and constructive feedback from resource persons who are experts in Public Speaking. The results of the training showed significant improvements in several aspects: participants' confidence increased, communication skills developed, critical thinking and argumentation skills improved, and participation in school activities increased. The pre-test and posttest results showed a significant improvement in skills after the training. Positive feedback from participants supported the effectiveness of the interactive and inclusive training methods. The training not only provided individual benefits but also strengthened dynamics and co-operation among students. In conclusion, the training was successful in creating young people who are more prepared and confident in facing future challenges, and is recommended to be continued periodically with continuous mentoring and involving various resource persons.